Recent advances in graphene nanoribbons for biosensing and biomedicine. Issue 31 (22nd July 2021) - Luo, Siyu; Chen, Xi; He, Yihan; Gu, Yingqiu; Zhu, Chengzhou; Yang, Guo-Hai; Qu, Lu-Lu
Abstract : A focus review on the recent advances in graphene nanoribbon-based nanomaterials for biosensors and biomedicine is presented. Abstract : In recent years, a new type of quasi-one-dimensional graphene-based material, graphene nanoribbons (GNRs), has attracted increasing attention. The limited domain width and rich edge configurations of GNRs endow them with unique properties and wide applications in comparison to two-dimensional graphene. This review article mainly focuses on the electrical, chemical and other properties of GNRs, and further introduces the typical preparation methods of GNRs, including top-down and bottom-up strategies. Then, their biosensing and biomedical applications are highlighted in detail, such as biosensors, photothermal therapy, drug delivery, etc. Finally, the challenges and future prospects in the synthesis and application of functionalized GNRs are discussed. It is expected that GNRs will have significant practical use in biomedical applications in the future.